Blockholder Heterogeneity, CEO Compensation, and Firm Performance - Clifford, Christopher P.; Lindsey, Laura (Journal of Financial and Quantitative Analysis, 2016)
This paper examines heterogeneity in blockholder monitoring across investor types. We document which blockholder types (e.g., mutual funds, hedge funds) are more likely to be associated with active monitoring and show that firms targeted by such blockholders are more likely to increase the equity portion of chief executive officer (CEO) pay. Further, using market-wide and exogenous shocks to liquidity to identify differences in efficacy across blockholder types, we observe greater operating-performance improvements in actively monitored firms when passive monitoring is less effective, suggesting causal impact. We propose differences in compensation arrangements across blockholder types as a mechanism underlying blockholders’ heterogeneous role.